Strategies for the Total Synthesis of Fucoxanthin from a Commercial Perspective - Gupta, Sayan Dutta; Pan, Cheol-Ho (SynOpen, 2024)
Fucoxanthin, the light-harvesting pigment of various algae, has shown promising biological activity in pre-clinical and clinical models. It has also received marketing approval as a nutraceutical and cosmetic ingredient in the USA and other countries. The commercial synthesis of this natural ingredient assumes significance because of various drawbacks (low yield, patent infringement, longer duration of cultivation, etc.) associated with its extraction and isolation procedures. This review is intended to provide an appraisal of the total syntheses of fucoxanthin reported to date along with a detailed explanation of the commercially viable approach. Finally, we briefly discuss the future of research for the total synthesis of fucoxanthin.
Keywords: fucoxanthin; total synthesis; commercialization